Levered returns and capital structure imbalances - Filippo Ippolito; Roberto Steri; Claudio Tebaldi; Alessandro T. Villa (Federal Reserve Bank of Chicago, 2022)
We revisit the relation between equity returns and financial leverage through the lens of a dynamic trade-off model with costly capital structure rebalancing. The model predicts that expected equity returns depend on whether a firm's leverage is above or below its target leverage. We provide empirical evidence in support of the model predictions. Controlling for leverage, overlevered (underlevered) firms earn higher (lower) returns. A quantitative version of our model reproduces key facts about capital structure rebalancing and equity returns for U.S. corporations. Overall, our results indicate that financial flexibility crucially affects the link between leverage and equity returns.
Keywords: G12; G32; 330; leverage; cross section of returns; target leverage; dynamic capital structure; financial frictions